2018
DOI: 10.1186/s12883-018-1101-9
|View full text |Cite
|
Sign up to set email alerts
|

Can the health related quality of life measure QOLIBRI- overall scale (OS) be of use after stroke? A validation study

Abstract: BackgroundBrief measures of health-related quality of life (HRQOL) that assess both patient-reported functioning and well-being after stroke are scarce. The objective of this study was to examine reliability and validity of one of these measures, the patient-reported Quality of Life after Brain Injury–Overall Scale (QOLIBRI-OS), in patients after stroke.MethodsStroke survivors were examined prospectively using survey methods.Core survey data (n = 125) and retest data (n = 36) were obtained at 3 and 12 months, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
(64 reference statements)
0
3
1
Order By: Relevance
“…The reworded QOLIBRI-OS is essentially an instrument for satisfaction with quality of life and further research is needed to investigate the psychometric properties of the reworded QOLIBRI-OS used in the general population. Preceding studies have found higher test-retest reliability of the QOLIBRI-OS in TBI [34] and stroke [35] patients than in our study population. This may indicate that the (reworded) QOLIBRI-OS is more sensitive in the injured population than in the general population.…”
Section: Discussioncontrasting
confidence: 63%
“…The reworded QOLIBRI-OS is essentially an instrument for satisfaction with quality of life and further research is needed to investigate the psychometric properties of the reworded QOLIBRI-OS used in the general population. Preceding studies have found higher test-retest reliability of the QOLIBRI-OS in TBI [34] and stroke [35] patients than in our study population. This may indicate that the (reworded) QOLIBRI-OS is more sensitive in the injured population than in the general population.…”
Section: Discussioncontrasting
confidence: 63%
“…Developing the QOLIBRI-OS involved literature reviews, qualitative focus group analyses, and quantitative psychometric analyses. 5,8,13 The QOLIBRI-OS has been translated into and validated for more than 10 languages, 8,[14][15][16][17][18][19] and it has been used internationally in research and clinical practice. 3,8,15 So far, only 1 study has provided a cutoff value for the QOLIBRI-OS to identify impairment in disease-specific HRQoL based on European TBI samples.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of three scales: the degree of experienced autonomy, the effort made to achieve autonomy, and dilemmas that doing what is best for the illness might not match a person's valued activities and social roles ( 21 ). The QOLIBRI measures the health-related quality of life in people with acquired brain injury with 37 items from 6 subscales ( 22 ). An overview of the primary and secondary outcome measures is presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%